Structural studies of phase behavior in 1,6-dicyanohexane/urea and 1,6-diisocyanohexane/urea inclusion compounds - Alquist, Keith Eldred III (Kansas State University, 2014)
The crystal structures of the inclusion compounds 1,6-diisocyanohexane/urea and 1,6-dicyanohexane/urea were refined at several temperatures from X-ray data. These urea inclusion compounds are commensurate structures with host:guest ratios of 6:1. In contrast with the ordinary helical topology of the urea host, these structures have stacked loop topologies of the host hydrogen bonds and crystallize in space group P21/n. At room temperature, both structures are distorted along [001] from hexagonal metric symmetry. As in earlier studies of 1-chloro-6-cyanohexane/urea, cooling 1,6-diisocyanohexane/urea gives rise to an exothermic phase transition (Hº = -856 cal mol 1, Sº = -5 cal mol-1 K-1) at 175 K that results in the cooperative translation of guest molecules by 5.5 Å along the channel axis. In the low temperature form, 1,6-diisocyanohexane/urea is distorted along [100], much like X(CH2)6Y, where X, Y = Br, Cl. Although the crystal structure of 1,6-dicyanohexane/urea is essentially isomorphous with that of the high temperature form of 1,6-diisocyanohexane/urea, it does not undergo an equivalent phase transition at low temperatures. Both of these systems exhibit dynamic disorder between two gauche conformers of the guest, which have mean planes of the alkyl chains lying within 1º of [100] (major conformer) and approximately 14º from [001] (minor conformer). The temperature dependence of site occupancy factors for the disordered sites yielded enthalpy differences between major and minor sites in 1,6-diisocyanohexane/urea and 1,6-dicyanohexane/urea of 216 and 127 cal mol 1, respectively. Since the low temperature form of 1,6-diisocyanohexane/urea is distorted along [100], this is favored at low temperatures by an increased concentration of the major conformer, which predominates in 1,6-dibromohexane/urea and congeners. In 1,6-diisocyanohexane/urea, the phase transition to the low temperature form occurs at a threshold concentration for the major conformer of 67%. With its shallower temperature dependence, 1,6-dicyanohexane/urea should not reach this threshold population until approximately 92 K, at which temperature the system cannot overcome the barrier for cooperative translation of guests along the channel axis.
Keywords: Chemical crystallography; Guest transport; Inclusion compound; Urea inclusion compound; Guest jump angle; Solid state transport; Chemistry (0485)